Analysis on the risks of severe adverse events in rabies post-exposure prophylaxis and appropriate decision-making procedure - Shichun Huang; Zhenggang Zhu; Li Cai; Zerong Zhu; Man Zhang; Quan Hu; Yuan Fang (Taylor & Francis Group, 2019)
Severe adverse events (AEs) following post-exposure rabies vaccination had been occasionally described in previous studies. Once AEs occurred, immediate medical treatment and appropriate change of vaccine and vaccination schedule were of significance. It was also important and challengeable to determine the relationship among adverse reactions, vaccines residues and laboratory tests for patients, to choose a proper vaccine in resumed vaccination, to avoid the reoccurrence of AEs and to ensure adequate immune response. Here, we present steps about how to cope with AEs by giving an example with a two-year-old girl who was identified as category II exposure to rabies, suffered from anaphylaxis after first dose administration with human diploid rabies vaccine (HDCV) so vaccination was temporarily suspended. Dexamethasone was prescribed to her in anti-allergy therapy. Allergy tests indicated that the patient was not sensitive to allergens and heterologous proteins. Vaccine test report showed that residual kanamycin existed in that batch of vaccines. This reminded us to provide her antibiotic skin sensitivity test which found she was allergic to kanamycin. Thus, we could conclude it was the cause of AEs. Then, 0.5 mL lyophilized Purified Vero Cell Rabies Vaccine (PVRV) without any residues was enrolled in the resumed vaccination. To ensure successful immunization, immunogenicity test was also provided which showed adequate immune response (RVNA ≥ 0.5 IU/mL) starting from day14. Besides, no further AEs occurred afterward. This study emphasized the importance of in-depth survey, analysis and implied the necessity to scientifically and properly choose the optimal vaccine for patients and appropriately provide treatments if AEs occurred.